TRANSFORMASI DIGITAL: LAYANAN PRODUK & PROMOSI UNTUK UMKM (USAHA MIKRO, KECIL, DAN MENENGAH) DI SMK KEHUTANAN SOBAT BUMI, KAWALU KOTA TASIKMALAYA - Jeffry Nugraha; Sutopo Sutopo; Adie Pamungkas; Hana Diana Maria (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service activity, organized by the Digital Business Study Program of the Faculty of Technology and Business at Universitas Bakti Tunas Husada, focuses on increasing digital literacy and promoting digital transformation among local Small and Medium Enterprises (SMEs) in Kelurahan Urug, Kawalu, Tasikmalaya. The activity aims to enhance the competitiveness of local businesses by introducing Artificial Intelligence (AI) tools for digital marketing and product promotion. The participants, consisting of farmers, SME owners, and community members, received insights on leveraging digital marketing platforms and AI to improve the visibility and reach of their products. The program successfully engaged the participants through interactive discussions and practical demonstrations, fostering a deeper understanding of how digital transformation can boost their businesses. The results indicate a strong motivation among the community to continue utilizing digital tools, ensuring the sustainability of this initiative.